HOW TO DISPEL THE FOG OVER THE PAST? POST-WAR CHILDREN, THEIR FATHERS-SOLDIERS AND CONSEQUENCES OF THE SECOND WORLD WAR - E. S. Lyubomirova (Vestnik MGIMO-Universiteta)
The article is devoted to the new aspects in the study of the history of post-war Germany, revealed in the book written by Sabine Bode «Post-war children - born in the 1950s, and their fathers-soldiers». It discusses the contribution made by Bode in the study of mental and psycho-emotional consequences of the Second World War and the «exclusion of the past», which is reflected in the fate of the post-war children and continues to have an impact on the socio-political life of the Federal Republic of Germany up to the present day. Nevertheless the article criticizes an excessive preoccupation of the monograph with the descriptions of the individual biographies to the detriment of analysis.